Factors Influencing Events Dysfunction Cognitive Post Operation on Patient Elderly: Systematic Review - Kusuma, Ratna; Veibiani, Nindita Arum (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: : Improvements in global life expectancy have led to a significant increase in the elderly population, which in turn results in a growing number of elderly patients undergoing surgery. This condition raises the risk of postoperative complications, such as postoperative cognitive dysfunction (POCD). POCD can reduce quality of life, prolong the length of hospital stay, and increase mortality. This study aims to identify and synthesize the factors that influence the occurrence of POCD in elderly patients. Subjects and Method: This study is a Systematic review with PICO. The article used in research were obtained from several databased including Google Scolar, Scopus, and PubMed Keywords to find articles are